Facile Low-Cost Synthesis of Highly Photocatalitycally Active Zinc Oxide Powders - Kedruk, Y. Y.; Baigarinova, G. A.; Gritsenko, L. V.; Cicero, G.; Abdullin, Kh. A. (Frontiers in Materials, 2022)
The industrial waste can cause significant harm to human health and to the environment. Organic dyes in particular are environmentally dangerous since they may cause the death of aquatic life or contaminate the feed chain. Thus, one of the current research fields consists of the development of an inexpensive and environmentally friendly method to purify wastewater from organic contaminants. Among the others, Zinc oxide (ZnO) is considered one of the most effective photocatalysts for the decomposition of organic pollutants in water. In this work, we developed a highly efficient low-temperature and environmentally safe synthesis method to obtain photocatalytically active nanostructured ZnO by chemical precipitation from a solution. The effect of the technological conditions of synthesis on the photocatalytic properties is considered in detail, the correlation with the morphology, structural, and optical properties of the synthesized ZnO samples is determined. It was found that the maximum photocatalytic activity with respect to the decomposition of the dye rhodamine-B (RhB) is achieved for samples synthesized at NaOH molar concentration from 0.4 M to 0.7 M; while the sizes of crystallites along the 100 and 101 directions decrease monotonically from 30 to 25 nm as the NaOH molar concentration increases from 0.14 M to 1 M.